Study on Mechanical, Physical and Thermal Properties of Oil Palm Mesocarp Fiber Composite with Eco-Friendly Sodium Bicarbonate Treatment of Fiber - Bakri, Bakri; Fadly, Muhammad Syaiful; Chandrabakty, Sri; Padang, Antonius Medi Lili (Engineering Transactions, 2026)
This article studied the effect of variation of sodium bicarbonate (NaHCO3) concentration fiber treatment on the mechanical, physical, and thermal properties of oil palm mesocarp fiber (OPMF) composite. The components of the OPMF composite are OPMF and polyester resin. OPMF composite was fabricated by hand lay-up, followed by the compression method. Before composite fabrication, the treatment of OPMF was conducted by NaHCO3 concentration variation, including 8 wt%, 10 wt%, and 12 wt%. Mechanical testing (tensile and flexural), physical testing (water absorption and thickness swelling), and thermal testing were performed. Scanning electron microscopy (SEM) verified the composite’s surface tensile fracture. The results show that the mechanical properties of the OPMF composite have improved after NaHCO3 treatment. 12 wt% treatment produces the best mechanical properties. Then, the physical and thermal properties of the composite with 12 wt% treatment were found to be the best, with the lowest swelling and thermal stability, respectively.